The role of corporate leniency policy in the law enforcement against cartels in the United States, European union and South Africa: lessons for the United Republic of Tanzania - Chanzi, Zainab (Centre for Law and Society, 2026)
Cartel practices such as price fixing, market division and bid rigging are very secretive in nature. Moreover, fighting against cartel is one of the tasks which have been given priority by competition authorities all over the world However, competition authorities are facing significant difficulties in detecting and successful prosecuting members of cartel due to the said secretive nature which surrounds the members of the cartel. On the other hand, the introduction of Corporate Leniency Policy has proved to be one of the effective mechanisms which can assist competition authority in the fight against cartels. The purpose of this paper is therefore to show how Corporate Leniency Policy has assisted United States, European Union and South Africa to unearth cartels and prosecute members of cartel practices. It also explores cartel practices in Tanzania and their effects to the economy and consumers. It further demonstrates that it is worth to introduce Corporate Leniency Policy in Tanzania so as to enable the Fair Competition Commission to fight against cartels.